2008
DOI: 10.1074/jbc.m708934200
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GLUT4 Translocation by Tbc1d1, a Rab GTPase-activating Protein Abundant in Skeletal Muscle, Is Partially Relieved by AMP-activated Protein Kinase Activation

Abstract: Insulin increases glucose transport by stimulating the trafficking of intracellular GLUT4 to the cell surface, a process known as GLUT4 translocation. A key protein in signaling this process is AS160, a Rab GTPase-activating protein (GAP) whose activity appears to be suppressed by Akt phosphorylation. Tbc1d1 is a Rab GAP with a sequence highly similar to that of AS160 and with the same Rab specificity as that of AS160. The role of Tbc1d1 in regulating GLUT4 trafficking has been unclear. Our previous study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
123
3
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 30 publications
11
123
3
2
Order By: Relevance
“…As shown in Figure 2A, as differentiation progressed, RUVBL2 was increasingly upregulated (Supplementary information, Figure S1). However, the expression of AS160 reached a plateau at day 4 of differentiation and declined thereafter, consistent with a previous report [11]. RUVBL2 expression levels in epididymal fat tissues of obese insulin-resistant diabetic KKAy mice and C57BL/6J control mice were compared, and RUVBL2 expression was found to be markedly reduced in fat tissues of obese insulin-resistant diabetic KKAy mice (Figure 2B).…”
Section: Ruvbl2 Is Highly Expressed In 3t3-l1 Adipocytessupporting
confidence: 76%
“…As shown in Figure 2A, as differentiation progressed, RUVBL2 was increasingly upregulated (Supplementary information, Figure S1). However, the expression of AS160 reached a plateau at day 4 of differentiation and declined thereafter, consistent with a previous report [11]. RUVBL2 expression levels in epididymal fat tissues of obese insulin-resistant diabetic KKAy mice and C57BL/6J control mice were compared, and RUVBL2 expression was found to be markedly reduced in fat tissues of obese insulin-resistant diabetic KKAy mice (Figure 2B).…”
Section: Ruvbl2 Is Highly Expressed In 3t3-l1 Adipocytessupporting
confidence: 76%
“…Prolonged AMPK activation has been reported to inhibit differentiation of pre-adipocytes into mature adipocytes with an associated reduced protein production of several enzymes concerned with lipid metabolism, namely ACC, fatty acid synthase (FAS) and peroxisome proliferator-activated receptor (PPAR)γ [13]. In addition, we and others have reported that AMPK activation is associated with reduced insulinstimulated glucose transport in adipocytes [14][15][16], although a conflicting study has reported no effect of AMPK stimulation when assessing translocation of the insulinsensitive glucose transporter, GLUT4 [17]. Several physiological and pharmacological stimuli have been reported to stimulate rodent adipose tissue AMPK, including exercise, starvation, troglitazone and adrenaline (epinephrine) [10,[18][19][20], whereas AMPK is inhibited in response to ghrelin, corticosterone and a high-fat diet [21][22][23] in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…TBC1D1 is a Rab-GTPase activating protein that has been linked to obesity and its inactivation leads to a "lean" phenotype with increased glucose transport and fatty acid oxidation in tissues, especially skeletal muscle (Chadt et al, 2008;Frosig et al, 2010). TBC1D1 is also known to be phosphorylated at serine 237 by AMPK (Chavez et al, 2008), although the functional significance of AMPKdependent phosphorylation on TBC1D1 activities, such as glucose transport, is unknown. Considering the metabolic similarities between mice with conditional postnatal ablation of TDP-43 and mSOD1 transgenic mice, we wondered whether TBC1D1 activity is decreased in our mSOD1 models and whether the beneficial effects of reduced AMPK activity are associated with alterations in TBC1D1 activity.…”
Section: Rnai Knockdown Of Aak-2 In Neurons Improves Locomotor Behaviormentioning
confidence: 99%